TINJAUAN KETERAMPILAN TEKNIK DASAR SEPAKBOLA PADA SSB WONER 2012 PEKANBARU - ', Dorisman; ', Ramadi; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research is based on observations that have been conducted to the football players on SSB Woner 2012 Pekanbaru, which could be found some problems that there were still many players who were not skilled in soccer base technique skills as well as in doing dribbling the ball, passing and stopping the ball, heading and shooting the ball. It could be seen when players dribbled the ball, their foot positions and movements were stiff, hence it could make less perfect and less controlled when they were dribbling the ball. The player?s skill of passing and stopping were also low. It could be seen when a player put improperly the ball, so the ball was not up to the right friend. Then, the skill of the shooting was low, their kick was rather not powerful or slow, so it was easily anticipated by the opponent goalkeeper. Next, the player heading skill was still insufficient; it could be seen from the player?s difficulty in heading the ball that had been lured by a friend. The purpose of the research is to determine the basic techniques of soccer skills in SSB Woner 2012 Pekanbaru.The type of research is Descriptive. Descriptive research is a research method that describes and interprets the object as the way it is and uses not separated sample. The population of this research is all athletes in SSB Pekanbaru Woner 2012 which consist of 20 players. The sampling technique is using Total Sampling technique. The sample used in this research is the athletes of SSB Pekanbaru Woner 2012 which consists of 20 players. The Results of research shows that the average of T score of the SSB Woner 2012 Pekanbaru athletes? skill is 50.18 which stated in the range of 46-52 which means Mediocre.Keywords: Review, soccer basic skill